Searching for Elko dark matter spinors at the CERN LHC - Alves, Alexandre; Campos, F. de [UNESP]; Dias, M.; Hoff da Silva, J. M. [UNESP] (World Scientific Publ Co Pte Ltd, 2015)
The aim of this paper is to explore the possibility of discovering a fermionic field with mass dimension one, the Elko field, in the Large Hadron Collider. Due to its mass dimension, an Elko can only interact either with Standard Model spinors and gauge fields at one-loop order or at tree level through a quartic interaction with the Higgs field. In this Higgs portal scenario, the Elko is a viable candidate to a dark matter constituent which has been shown to be compatible with relic abundance measurements from WMAP and direct dark matter searches. We propose a search strategy for this dark matter candidate in the channel pp -> l(+)l(-) + is not an element of(T) at the root s = 14 TeV LHC. We show the LHC potential to discover the Elko considering a triple Higgs-Elkos coupling as small as similar to 0.5 after 1 ab(-1) of integrated luminosity. Some phenomenological consequences of this new particle and its collider signatures are also discussed.